12 essential skills for software architects - Hendricksen, Dave, 1964- (Addison-Wesley, 2011)
Master the Crucial Non -Technical Skills Every Software Architect Needs! Thousands of software professionals have the necessary technical qualifications to become architects, but far fewer have the crucial non -technical skills needed to get hired and succeed in this role. In today's agile environments, these "soft" skills have grown even more crucial to success as an architect. For many developers, however, these skills don't come naturally-and they're rarely addressed in formal training. Now, long-time software architect Dave Hendricksen helps you fill this gap, supercharge your organizational impact, and quickly move to the next level in your career. In 12 Essential Skills for Software Architects, Hendricksen begins by pinpointing the specific relationship, personal, and business skills that successful architects rely upon. Next, he presents proven methods for systematically developing and sharpening every one of these skills, from negotiation and leadership to pragmatism and vision. From start to finish, this book's practical insights can help you get the architect position you want-and thrive once you have it! The soft skills you need... ...and a coherent framework and practical methodology for mastering them! Relationship skills Leadership, politics, gracious behavior, communication, negotiation Personal skills Context switching, transparency, passion Business skills Pragmatism, vision, business knowledge, innovation.